RANCANG BANGUN TUTORIAL MATA PELAJARAN IPA BAGI SISWA SEKOLAH DASAR (Information Technology and Telematics, 2014)
Abstract - Education is an institution that is essential to building characteristics, mindset and intelligence of a person. learning media is an educational institution for students to acquire science and knowledge. Education determines the quality of the nation. In addition to this quiz is also a means of  learning which are quite effective, the quiz is necessary in the education aspects, with quizzes their can indirectly assess the development of  knowledge, skills or expertise. This research combining between educational aspect and quiz that will produce a quiz contained lecture tested the national exam elementary school to be used as a medium of learning that are mobile.Application quiz pre-prosperous national examination this made by using android developer tools.While for databases used is sqlite that is a database open source embedded in android. This research resulted in a quiz application provides lecture that can be tested at the level of primary school. This application comes with a notification if the selected answer is right or wrong and limited by time has been set. Keywords: elementary school quiz, android quiz, national exam quiz.